Glutathione S-transferase M1 null genotype as a risk factor for carbamazepine-induced mild hepatotoxicity. (May 2007) - Ueda, Kentaro; Ishitsu, Takateru; Seo, Takayuki; Ueda, Nao; Murata, Tsukasa; Hori, Masaharu; Nakagawa, Kazuko
The aim of this study is to verify whether the combination of glutathione S -transferase (GST) M1 null and GSTT1 null genotypes, which is a candidate genetic risk factor for troglitazone-induced liver failure, is common to that for the carbamazepine-induced mild hepatotoxicity.Patients & methods: The genotypes of GSTM1 and GSTT1, and microsomal epoxide hydrolase-3 and -4, were determined in 192 Japanese epileptics treated with carbamazepine.Results: The GSTM1 null ( GSTM1 -) and GSTT1 null ( GSTT1 -) genotypes in the subjects were 55.7 and 39.6%, respectively. The alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels were elevated in 46 (24.0%) and 62 (32.3%) cases, and the mean values were approximately 2.3- and 1.8-times higher than the upper limit of normal levels, respectively. The levels of ALT and AST were significantly higher in GSTM1 - than in GSTM1 present ( GSTM1+ ) genotypes (p = 0.007 and 0.004, respectively). The level of ALT was significantly higher in GSTM1-/T1- than in GSTM1+/T1- and GSTM1+/T1+ (p = 0.01 and 0.01, respectively), and that of AST was significantly higher in GSTM1-/T1- and GSTM1-/T1+ than in GSTM1+/T1+ (p = 0.02 and 0.003, respectively). The microsomal epoxide hydrolase genotype did not influence the hepatotoxicity.Conclusion: These findings suggested that GSTM1- rather than GSTM1-/T1- was a risk factor for carbamazepine-induced mild hepatotoxicity.